Revisiting the Group-dominant Elliptical NGC 5044 in the Radio Band: Continuum Emission and Detection of H i Absorption - Kamlesh Rajpurohit; Tirna Deb; Konstantinos Kolokythas; Kshitij Thorat; Ewan O’Sullivan; Gerrit Schellenberger; Laurence P. David; Jan M. Vrtilek; Simona Giacintucci; William Forman; Christine Jones; Mpati Ramatsoku (The Astrophysical Journal)
We present new MeerKAT L -band (continuum and H i ) and upgraded Giant Metrewave Radio Telescope (300–850 MHz) observations of the archetypal cool-core group-dominant early-type galaxy NGC 5044. Our new continuum images reveal diffuse, steep spectrum ( ${α }_{0.99\,{\rm{GHz}}}^{1.56\,{\rm{GHz}}}=-1.53± 0.6$ ) radio emission extending about 25 kpc around the unresolved radio core. The observed radio emission overlaps the known X-ray cavities but is not confined to them. We also find the first direct evidence of neutral atomic gas in NGC 5044, in the form of a 3.8 σ significant two-component H i absorption line seen against the emission of the active nucleus. The peak velocities are well correlated with the previously reported CO(2–1) absorption, but the H i lines are moderately broader, spanning velocities from 265 to 305 km s ^−1 . We do not detect H i emission but place an upper limit of M _H _i < 5.4 × 10 ^7 M _⊙ in the central 15″ (2.2 kpc) of the galaxy. This is significantly less than the estimated molecular gas content and implies a molecular-to-atomic mass ratio of >∼1.7:1, consistent with these gas phases forming through cooling from the hot intra-group medium. We also constrain the spin temperature to T _spin ≤ 950 K, indicating that the detected H i is in the cold neutral phase.